Study of the mechanism of action of the antimicrobial peptide rBPI21 in gram-negative bacteria - Domingues, Marco André Manso, 1985- (2013)
Tese de doutoramento, Ciências Biomédicas (Bioquímica Médica), Universidade de Lisboa, Faculdade de Medicina, 2012